Can Social Protection Reduce Environmental Damages? - Teevrat Garg; Gordon C. McCord; Aleister Montfort (Institute of Labor Economics (IZA), 2020)
Why do damages from changes in environmental quality differ across and within countries? Causal investigation of this question has been challenging because differences may stem from heterogeneity in cumulative exposure or differences in socioeconomic factors such as income. We revisit the temperature-violence relationship and show that cash transfers attenuate one-half to two-thirds of the effects of higher same-day temperatures on homicides. Our results not only demonstrate causally that income can explain much of the heterogeneity in the marginal effects of higher temperatures, but also imply that social protection programs can help the poor adapt to rising temperatures.
Keywords: Q50; Q52; Q54; Q58; I14; 330; cash transfers; temperature; violence